Benchmark Framework for a Load Balancing Single System Image - Ahmed, Bestoun S.; Samsudin, Khairulmizam; Ramli, Abdul Rahman (2008)
Recent developments in the load balancing single system image (SSI) clusters enabled workstations to provide a cost effective and high performance environment which has become increasingly attractive to many users. However, in practice, clusters of workstation failed to exploit their performance potential advantages. This paper presents and propose a framework for benchmarking and performance evaluation of a load balancing SSI and shows how this framework used as a methodology for a comprehensive examination of load balancing SSI clusters performance and behavior.